The Association of Male Pattern Baldness in Men with Benign Prostatic Hyperplasia - Al Edwan, Ghazi; Abufaraj, Mohammad; Al-Omari, Mohammad; Alemraryat, Tariq; Alnawaeseh, Hasan; Khamaiseh, Faris; Abuelbeh, Ibrahim; Sahouri, Jamel; Hamdan, Omar (Jordan Medical Journal, 2023)
Aim: To evaluate the association between male pattern baldness (MPB) and benign prostatic hyperplasia (BPH). Methodology: Cohort study, data collected by co-authors. All extracted data were input to Excel sheets and further imported into STATA version 14. The study’s results were reported in the form of descriptive statistics. Results: This study found no significant associations between MPB and BPH. Nonetheless, the study demonstrated that patients with increased baldness severity have higher rates of diabetes mellitus (DM) and obesity. Conclusion: There is no association between MPB and BPH.